Targeted cleavage of nad6 mRNA induced by a modified pentatricopeptide repeat protein in plant mitochondria. (December 2018) - Colas des Francs-Small, Catherine; Vincis Pereira Sanglard, Lilian; Small, Ian
Abstract Mitochondrial genes encode key components of the cellular energy machinery, but their genetic analysis is difficult or impossible in most organisms (including plants) because of the lack of viable transformation approaches. We report here a method to block the expression of the mitochondrialnad6 gene encoding a subunit of respiratory complex I inArabidopsis tha liana, via the modification of the specificity of the RNA-binding protein RNA PROCESSING FACTOR 2 (RPF2). We show that the modified RPF2 binds and specifically induces cleavage ofnad6 RNA, almost eliminating expression of the Nad6 protein and consequently complex I accumulation and activity. To our knowledge, this is the first example of a targeted block in expression of a specific mitochondrial transcript by a custom-designed RNA-binding protein. This opens the path to reverse genetics studies on mitochondrial gene functions and leads to potential applications in agriculture. Catherine Colas des Francs-Small et al. used an engineered pentatricopeptide repeat protein to induce cleavage ofnad6 mRNA in the mitochondria ofArabidopsis thaliana, eliminating its expression. The approach has potential for use in functional characterization of mitochondrial genes and future agricultural applications.